Assessment of Potential Area for Solar Energy Investment in Northeastern Thailand by Entropy-TOPSIS Method - Phonphoon, Phichata; Kiatcharoenpol, Tossapol; Klongboonjit, Sakon (My University, 2024)
Agriculture is one of the important engines of Thailand's food industrial growth however the cost of fossil energy is quite high for Thai farmers. Since Thailand has great solar potential, especially northeastern region, renewable energy sources of sunlight in this region should be considered to be another energy source for Thai agriculture. To assess and classify the potential of the investment in agricultural solar power systems of 20 provinces in Thailand's northeastern region, this study applied the combining method of Entropy Weight Method and TOPSIS with secondary data of solar irradiance, farmer household density, and income of farmer households. With this combining method, the results showed that farmer household density and income of farmer household were more influence on assessing and classifying the potential of this investment than solar irradiance. Finally, all 20 provinces were classified into four groups of Group A (A12, A2, A4, A1, and A10), Group B (A8, A9, A19, A3, and A15)), Group C (A17, A13, A18 A16, and A20) and Group D (A6, A11, A7, A14, and A5) from the most potential province group for investment in agriculture solar power system to the least potential province group for investment in agriculture solar power system.
Keywords: agriculture; assessment; entropy weight method; solar power; TOPSIS